PSYCHOLOGICAL PHENOMENOLOGY OF STUDENT COMMUNICATION IN EDUCATIONAL AND PERSONAL CYBERSPACE - Гордієнко, Арсеній (SWorldJournal, 2024)
The article examines the peculiarities of student communication in the Internet space, presents the results of an empirical study, outlines the phenomenology of student activity and communication in the educational process (counterproductive and productiv